2022
DOI: 10.1155/2022/6716474
|View full text |Cite
|
Sign up to set email alerts
|

MALL and EFL Learners’ Speaking: Impacts of Duolingo and WhatsApp Applications on Speaking Accuracy and Fluency

Abstract: Regarding the importance of using MALL in learning English, this study aimed to investigate the effects of Duolingo and WhatsApp applications on developing the speaking accuracy and fluency of Iranian EFL learners. To fulfill this objective, three groups of Iranian intermediate EFL learners were selected as the participants of this research. After that, all groups took the speaking pretest and then received the treatment. One group was taught ten conversations from Family and Friends Book 5 using the Duolingo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Additionally, the study results go in line with the findings of Kargozari's and Zarinkamar's (2014) study and Mashhadi's, Hayati's and Jalilifar's (2016) study illustrating that podcasts fostered EFL undergraduates' vocabulary. Furthermore, the current study results are consistent with the findings of Azeez and Albajalani (2018), Sobh (2018) and Ahmed et al (2022) highlighting that MALL fostered EFL speaking fluency. Additionally, the present study results go in line with the findings of Pardo-Soto and Cisterna-Zenteno (2019) indicating the positive impact of video recording speeches using smartphone applications on fostering EFL learners' speaking fluency.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the study results go in line with the findings of Kargozari's and Zarinkamar's (2014) study and Mashhadi's, Hayati's and Jalilifar's (2016) study illustrating that podcasts fostered EFL undergraduates' vocabulary. Furthermore, the current study results are consistent with the findings of Azeez and Albajalani (2018), Sobh (2018) and Ahmed et al (2022) highlighting that MALL fostered EFL speaking fluency. Additionally, the present study results go in line with the findings of Pardo-Soto and Cisterna-Zenteno (2019) indicating the positive impact of video recording speeches using smartphone applications on fostering EFL learners' speaking fluency.…”
Section: Discussionsupporting
confidence: 92%
“…After that, they are required to repeat the same speech to listeners in three minutes and then in two minutes to foster their fluency (Hoshino, 2012;Wang, 2014;Ghasemi & Mozaheb, 2021). In their turn, Ahmed et al (2022) found that using WhatsApp as well as Duolingo smartphone applications enhanced Iranian EFL adult learners' speaking fluency.…”
Section: Techniques Employed To Enhance Speaking Fluency Among Efl Le...mentioning
confidence: 97%
See 1 more Smart Citation
“…Ahmed et al [33] explored the impact of the Duolingo and WhatsApp programs on the development of speaking accuracy and fluency among Iranian EFL learners. For this purpose, three groups of Iranian intermediate EFL learners were chosen as the participants.…”
Section: E Impact Of Mall On Speaking Skill Hadi and Emzirmentioning
confidence: 99%
“…In the field of English as a second/foreign language (ESL & EFL), there has been a growing focus on integrating information technology into language learning and teaching. Many researchers have increasingly focused on investigating the integration of various language apps (such as Duolingo, Hellotalk, and WhatsApp) into English learning and teaching (Ahmed et al, 2022;Sadeghi and Chalak, 2023;Sakkir and Syamsuddin, 2023). Recently, a surge in the number of studies conducted has consistently highlighted the significant efficacy of MALL as an effective tool for language learners.…”
Section: Mobile Assisted Language Learning (Mall)mentioning
confidence: 99%